The impact of blockchain adoption on competitive performance: the mediating role of process and relational innovation. Issue 1 (2nd January 2020) - Fosso Wamba, Samuel; Guthrie, Cameron
ABSTRACT: While Blockchain is heralded as an industry 'game changer', empirical studies have yet to demonstrate how it has positive performance impacts. Building on emerging blockchain research and the information technology adoption literature, this study develops a research model that links blockchain adoption in the supply chain to competitive performance through process innovation and relational innovation. The study uses data collected from 344 supply chain professionals working in companies with Blockchain experience and partial least squares modelling to test the proposed model. The results support the research model and confirm that competitive performance is directly improved through blockchain adoption and also indirectly through blockchain-enabled process and relational innovation. Our findings advance practice and theory by contributing to the emerging literature on blockchain and enriching our understanding of the performance impacts of blockchain adoption and use in the supply chain.